PELUANG KERJA DAN BERUSAHA MASYARAKAT DENGAN BEROPERASINYA PEMBANGKIT LISTRIK TENAGA UAP (PLTU) DI RW 03 KELURAHAN TUAH NEGRI KECAMATAN TENAYAN RAYA KOTA PEKANBARU - Aulia Rahman; Jonyanis " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2020)
The establishment of PLTU in RW 03 affects the surrounding community. In this case the change studied is economic change, economic change will bring economic impacts and social impacts to the surrounding community. Socioeconomic changes that occur can be seen from several aspects, among others: changes in relationships between individuals, changes in behavior patterns, changes in livelihoods and changes in the level of income in society. The problems taken in this study are: (1) What job opportunities are open to the community around the Tenayan Raya power plant ?, (2) What business opportunities are open to the community around the Tenayan Raya power plant ?. This study aims: (1) What job opportunities are open to the community around the Tenayan Raya PLTU, (2) What business opportunities are open to the community around the Tenayan Raya PLTU? The location of this research is RW 03 Kec. Tenayan Raya Pekanbaru City. The method used is descriptive quantitative method. The population in this study is the people who live in RW 03 before the construction of the power plant. The sample of this study were 175 Family Cards (50%) of the entire population using simple random sampling. The results of the study explained that the construction of the Tenayan Raya PLTU was to meet the electricity supply in the community, especially for the Central Sumatra region. The construction of the power plant directly or indirectly has an effect on the socio-economic life of the community. The establishment of PLTU creates new jobs in the community. Residents who used to work mostly as farmers now prefer to work at the PLTU even though it is only a rough laborer. Besides the establishment of the PLTU also led to service businesses such as boarding houses and stalls aimed at providing the needs of migrant residents who worked at the PLTU. Changing people's livelihoods automatically leads to increased income in the community. The presence of migrants who live in RW 03 does not significantly affect the lives of local residents.Keywords : Job Opportunities, Business Opportunities